Nathaniel Hawthorne's The scarlet letter - Bloom, Harold (New York : Chelsea House Publishers, 1986)
A collection of seven critical essays on Hawthorne's novel, arranged in chronological order of original publication.
Includes index.
Bibliography: p. 133-135.
Keywords: Hawthorne, Nathaniel, -- 1804-1864.; Hawthorne, Nathaniel, -- 1804-1864.; Mothers and daughters in literature; Puritans in literature; Adultery in literature; Women in literature; American literature -- History and criticism; Massachusetts -- In literature